Information Needs Among Indonesian People Related to COVID-19 - Rokhmayanti Rokhmayanti; Sulistyawati Sulistyawati; Budi Aji; Siwi Pramatama Mars Wijayanti (Procedia of Social Sciences and Humanities, 2021)
This is an online survey research of 816 respondents aged ≥ 18 years throughout Indonesia, aiming at analyzing the information seeking behavior during the COVID-19 pandemic in Indonesia. This is a descriptive analytic research with cross-sectional design, aiming at describing the information seeking behavior of Indonesian people during the COVID-19 pandemic. The sociodemographic data and the respondents‘ information seeking behavior were analyzed descriptively, and then using the Chi-Square Test. Significant results (p<0,05) were found in the relationship between age and marital status with the information seeking behavior about the transmission of COVID-19 in Indonesia, the number of infected people in Indonesia, and the number of infected people in the world. This research results can be used as a reference for related parties in providing information about COVID-19 to be able to consider the age group and community marital status, thus it is expected to influence knowledge as well as to increase the behavior of preventing community against the COVID-19 transmission.